1995
DOI: 10.1111/j.1432-2277.1995.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous protein C deficiency and dysfibrinogenemia acquired by liver transplantation

Abstract: Orthotopic liver transplantation is now a successful treatment for end-stage liver diseases. Since most components of the coagulation system are synthesized by liver parenchymal cells, there is always a risk of genetic defects of hemostasis being transmitting by liver transplantation. Some coagulation factor defects, such as protein C deficiency, do not induce abnormalities in routine coagulation tests and, thus, go undetected before organ procurement. We report the first case, to our knowledge, of the transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…The patient described in the present report had congenital dysfibrinogenemia combined with FVII deficiency. There have been reports on congenital dysfibrinogenemia combined with FV Leiden mutation or protein C deficiency [13][14][15]. Our patient represents the first case of congenital dysfibrinogenemia combined with FVII deficiency confirmed by molecular genetic tests.…”
Section: Discussionmentioning
confidence: 56%
“…The patient described in the present report had congenital dysfibrinogenemia combined with FVII deficiency. There have been reports on congenital dysfibrinogenemia combined with FV Leiden mutation or protein C deficiency [13][14][15]. Our patient represents the first case of congenital dysfibrinogenemia combined with FVII deficiency confirmed by molecular genetic tests.…”
Section: Discussionmentioning
confidence: 56%
“…Both hemophilia A and B have been cured by liver transplantation [11], while factor XI deficiency has been acquired by this procedure [12]. Similarly, hypercoagulable states may also be affected by liver transplantation, insofar as heterozygous protein C deficiency and dysfibrinogenemia have been acquired by liver transplantation [13]. Conversely, APC resistance due to homozygous FV Leiden was corrected following liver transplantation for acute Budd-Chiari syndrome [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient represents the first reported case of Factor XII deficiency transmitted by orthotopic liver transplantation. Previous reports have documented liver donor‐to‐recipient transmission of protein C deficiency with dysfibrinogenemia, protein S, factor VII and factor XI deficiencies (1–4).…”
Section: Discussionmentioning
confidence: 99%
“…Some coagulation defects such as protein C, protein S and antithrombin III deficiency, which are not detected by routine coagulation tests such as the INR and aPTT could be undetected before organ procurement. One patient acquired heterozygous protein C deficiency and dysfibrinogenemia after liver transplantation, and this was associated with severe thrombotic complications (1). Schuetze et al reported a patient who acquired protein S deficiency after undergoing orthotopic liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation